Chemokines—What Is Their Role in Colorectal Cancer?. (20th February 2020) - Pączek, Sara; Łukaszewicz-Zając, Marta; Mroczko, Barbara
Colorectal cancer (CRC) is one of the leading causes of cancer-related death. It is the second most frequently diagnosed malignancy in Europe and third worldwide. Colorectal malignancies diagnosed at an early stage offer a promising survival rate. However, advanced tumors often present distant metastases even after the complete resection of a primary tumor. Therefore, novel biomarkers of CRC are sorely needed in the diagnosis and prognosis of this common malignancy. A family of chemokines are composed of small, secreted proteins. They are best known for their ability to stimulate the migration of several cell types. Some investigations have indicated that chemokines are involved in cancer development, including CRC. This article presents current knowledge regarding chemokines and their specific receptors in CRC progression. Moreover, the prime aim of this review is to summarize the potential role of these proteins as biomarkers in the diagnosis and prognosis of CRC.